The cognitive treatment components and therapies of cognitive behavioral therapy for insomnia: A systematic review. (December 2018) - Jansson-Fröjmark, Markus; Norell-Clarke, Annika
Summary: Since the beginning of the twenty-first century, there has been an increased focus on developing and testing cognitive components and therapies for insomnia disorder. The aim of the current review was thus to describe and review the efficacy of cognitive components and therapies for insomnia. A systematic review was conducted on 32 studies (N = 1455 subjects) identified through database searches. Criteria for inclusion required that each study constituted a report of outcome from a cognitive component or therapy, that the study had a group protocol, adult participants with diagnosed insomnia or undiagnosed insomnia symptoms or reported poor sleep, and that the study was published until and including 2016 in English. Each study was systematically reviewed with a standard coding sheet. Several cognitive components, a multi-component cognitive program, and cognitive therapy were identified. It is concluded that there is support for paradoxical intention and cognitive therapy. There are also other cognitive interventions that appears promising, such as cognitive refocusing and behavioral experiments. For most interventions, the study quality was rated as low to moderate. We conclude that several cognitive treatment components and therapies can be viewed as efficacious or promising interventions for patients with insomnia disorder. Methodologically stronger studies are, however, warranted.